Turkey Economic Monitor, October 2019 : Charting a New Course - World Bank (Washington, DC: World Bank, 2019)
The Turkish economy has experienced major external adjustments over the past 12 months, including declining current account imbalances, reduced external debt of banks, and a recovery in portfolio flows. These have lessened the external vulnerabilities that had accumulated in the run up to the August 2018 currency shock. These adjustments have reduced the country's external financing needs and contributed to a more stable Lira, notwithstanding bouts of currency volatility in 2019 Q2 and Q3. The adjustments were aided by somewhat agile policy responses and more favorable (than expected) global monetary conditions. Even so, foreign exchange reserves have gotten eroded over the past two years, exposing Turkey to external market pressure. The real sector remains deeply affected by the persistence of macro-financial vulnerabilities. Investment significantly decreased – contracting for four quarters in a row (till 2019 Q2) – whilst industrial production points to a weak turnaround. The gradual recovery from recession in 2018 H2 has been fueled by a pickup in private consumption and net external demand. The decline in inflation has begun, after exchange rate pass-through and episodes of loss of confidence in the Lira had sharply increased consumer prices, averaging 17 percent in the first three quarters of 2019. A gradual decline in producer prices since October 2018 has helped close the gap between PPI and CPI inflation and reduced pass-through pressures on consumer prices. Stagnating output levels, rising costs of production, and high consumer prices have led to significant job losses and falling real wages. Turkey's economy lost around 840 thousand jobs from May 2018 to May 2019, amounting to 2.9 percent of total employment. The unemployment rate increased from 10.6 percent to 14 percent between May 2018 and May 2019, with the youth seeing a jump in their unemployment rate from 19.6 to 25.6 percent. Average real wages declined by 2.6 percent between 2017 and 2018. The rise in unemployment and decline in real wages was experienced by workers across the skills and education spectrums. Poorer households have been the most impacted because many low-income workers are employed in construction and agriculture—the sectors that saw the biggest decline in jobs. Moreover, the long-term impact of a drop in real wages is significantly greater for the poorest households since they have limited coping mechanisms.